Preparation of porous carbon electrodes from semen cassiae for high-performance electric double-layer capacitors - Wei, Ji-Shi; Wan, Suige; Zhang, Peng; Ding, Hui; Chen, Xiao-Bo; Xiong, Huan-Ming; Gao, Shuyan; Wei, Xianjun (New journal of chemistry, 2018)
A series of sponge-like hierarchical porous carbons are prepared using semen cassiae as the precursor and potassium oxalate monohydrate as the activation agent. These sponge-like carbon materials have high surface areas, wide distributions of pore size, and the appropriate forms of nitrogen/oxygen derivatives. All these advantages in structures and surface states contribute to the outstanding performances of such materials as electrodes for high performance electric double-layer capacitors, which include high specific capacitance, high cycling stability, and high energy density. For example, the optimal sample exhibits a high specific capacitance of 401 F g −1 , excellent cycling stability (94.5% retention after 10 000 cycles), high energy density (12.01 W h kg −1 ) and a high power density (10 200 W kg −1 ) in 1 M H 2 SO 4 solution.